(untitled) (The Review of Diabetic Studies, 2025)
BACKGROUND: Egypt now ranks ninth out of ten nations in terms of the number of people with diabetes; by 2045, it is expected that the present number of 8.9 million (national prevalence 15.2%) would have doubled to 16.9 million, moving it up to position seven on the list. One of the first crops, flaxseed has been grown since the dawn of civilization. Commercial uses exist for all parts of the flaxseed plant, either raw or processed. Due to the possible health advantages linked to certain of its physiologically active components, flaxseed has garnered more attention in the area of food and disease research throughout the last 20 years. AIM: The purpose of this research was to determine how supplementing with flaxseed (Linum usitatissimum) affected the lipid profile of type 2 diabetes patients who were seen at the El Mahsama Family Practice Center in the Ismailia Governorate. SUBJECTS AND METHODS: A study including 146 T2DM patients who were seen at El Mahsama Family Practice Center was randomized, double-blind, and placebo-controlled. During six months, participants were randomized into two equal groups and given identical capsules containing either 30 g of flaxseed powder (30 g/day) or a placebo (30 g starch), in addition to their usual medical treatment. Follow-up was place at two, four, and six months. At baseline and every visit, lipid profile was measured. At p<0.05, statistical significance was established. Results: 30 gm daily Flaxseed supplementation showed significant reduction in LDL level (p=0.019) and triglycerides (p=0.012), alongside increased level of HDL (p=0.001). While the cholesterol level didn’t significantly affected (p=0.162). Conclusions: The present study observed a positive impact on the lipid profile, potentially lowering levels of LDL ("bad") cholesterol and triglycerides while potentially increasing HDL ("good") cholesterol. This is significant as dyslipidemia, an imbalance in blood fats, is a common co-morbidity associated with diabetes and increases the risk of cardiovascular complications.